Impaired Adaptive Motor Learning Is Correlated With Cerebellar Hemispheric Gray Matter Atrophy in Spinocerebellar Ataxia Patients: A Voxel-Based Morphometry Study - Bando, Kyota; Honda, Takeru; Ishikawa, Kinya; Takahashi, Yuji; Mizusawa, Hidehiro; Hanakawa, Takashi (Frontiers in Neurology, 2019)
To evaluate the degree to which parameters measured via a prism adaptation task are correlated with changes in cerebellar structure, specifically gray matter volume (GMV), in patients with spinocerebellar degeneration (SCD). We performed whole-brain voxel-based morphometry (VBM) analysis on 3-dimensional T1-weighted images obtained from 23 patients with SCD (SCD group) and 21 sex- and age-matched healthy controls (HC group). We quantified a composite index representing adaptive motor learning abilities in a hand-reaching task with prism adaptation. After controlling for age, sex, and total intracranial volume, we found group-wise differences in GMV and regional GMV correlations with the adaptive learning index. Compared with the HC group, the SCD group showed reduced adaptive learning abilities and smaller GMV in widespread regions of the cerebellum. In the SCD group, the adaptive learning index was correlated with cerebellar hemispheric atrophy in the right lobule VI and the left Crus I. We propose that the adaptive learning index reflecting prism adaptation represents functions of specific cerebellar regions. This index may be useful as a measure of cerebellar function in future SCD research.